(untitled) - Swan, Michael (New York, 1984)
Widely acclaimed by teachers and learners throughout the world, The Cambridge English Course has set new standards in course design. In three levels, from complete beginner to intermediate, it offers: - a thorough and complete course in around 100 hours per level - the original multi-syllabus course structure¼ex high levels of achievement - original, stimulating and varied topics - wide variety of exercise types¼ex exposure to authentic English right from the start - detailed, explicit guidance and support for the teacher - balanced coverage of all language skills Each level consists of a Student's Book, Practice Book (with or without key), Teacher's Book, Test Book, Class Cassette Set and Student's Cassette. Split editions of each of the Student's Books in three parts are available for added flexibility.
Keywords: English language; Study and teaching